165 Logistical demand of running a high-volume MRI service for patients with cardiac implantable electronic devices: findings from a 'one-stop' service model. (4th June 2021) - Dowsing, Benjamin; Bhuva, Anish; Cash, Lizette; Webb, Emily; Moon, James; Manisty, Charlotte
Abstract : Introduction: Patients with cardiac implantable electronic devices (CIEDs) should have access to Magnetic Resonance Imaging (MRI) when needed. Patients are still less likely to be referred and hospitals may not provide a service. A major barrier is reducing the logistical demand required at scale for a safe service. We aimed to quantify the logistical requirements of a high-volume Cardiac Device-MRI service. Methods: A single centre retrospective audit of a high-volume Cardiac Device-MRI service in a tertiary cardiac imaging unit in the UK. Six months of consecutive referrals from September 2020 were reviewed for patient and CIED details and barriers met. Referrals were sorted by source, indication, MR-Conditional labelling and referrer specialty. Results: 116 MRIs (48% cardiac, 52% non-cardiac) were performed on CIED patients in six months ( table 1 ). 53% were external referrals, 11% inpatient and 25% were suspected malignancy. Referrers were 47% cardiologists and 53% other specialty. Time from referral to scan was 15 days (interquartile range, IQR: 8 – 32). There were no complications.70% of referrals contained complete CIED details and 34% identified the CIED MR labelling. 17% were referred with incorrect MR-Conditional labelling and 8% with incorrect non-MR Conditional labelling. 7 additional days were required to obtain complete CIED details, 10% had delays over 2 weeks (0-145 days). A cardiac physiology department was contacted for 54%, involving 2 departments in 27%. For cancer referrals, obtaining correct details took 1 day longer compared to other referrals and required 2 extra emails to maintain provision within the national time to treatment targets of 62 days. Missing data was similarly present in referrals from Cardiologists and non-Cardiologists (59% versus 61% respectively). The non-Cardiologists recorded more incorrect CIED details (8% vs 0%) ( figure 1 ). External referrals required 17 days (11 – 42), compared to 14 (6 -35) days for internal referrals to obtain CIED information. Missing data was similarly present in external and internal referrals (67% versus 64%), and 35% required 3 or more repeat discussions with referrers after initial referral. Patients with non-MR Conditional CIED took 14 days longer to obtain complete referral details than MR-Conditional CIEDs. Even when referrers were aware of non-MR Conditional labelling, 41% required further discussion between patient and referrer regarding risks and benefits of MRI scanning. Conclusions: Both cardiology and non-cardiology referrers of patients with cardiac implantable electronic devices to MRI incorrectly classify MR-Conditional labelling. There is a large logistical burden to maintaining an MRI service for patients with CIEDs and may explain why some patients are not referred for MRI when required. An online referrals platform is under development to streamline this process, and institutional registration is available at www.mrimypacemaker.com. Conflict of Interest: Nil